Injection moulds for beginners - Dangel, Rainer (Hanser, 2016)
"This applications-oriented book describes the construction of an injection mould from the ground up. Included are explanations of the individual types of tools, components, and technical terms; design procedures; techniques, tips, and tricks in the construction of an injection mould; and pros and cons of various solutions. Based on a plastic part ("bowl with lid") specially developed for this book, easily understandable text and many illustrative pictures and drawings provide the necessary knowledge for practical implementation. Step by step, the plastic part is modified and enhanced. The technologies and designs that are additionally needed for an injection mould are described by engineering drawings. Maintenance and repair, and essential manufacturing techniques are also discussed."--Resumé vydavatele
Přeloženo z němčiny
Keywords: vstřikovací formy; vstřikování plastů; injection moulds; injection moulding; příručky; handbooks and manuals